Pendidikan Rasa Aman dan Tenteram Masyarakat Perspektif Siyasah Dusturiah: Analisis Tanggung Jawab Kepolisian pada Masyarakat Tasikamalaya Indonesia - Al Aziz, Alfandy Faris; Fautanu, Idzam; Rizal, Lutfi Fahrul (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study explores the responsibility of the Tasikmalaya Police Resort in ensuring public safety and order, based on Law Number 2 of 2002 concerning the Indonesian National Police, and viewed through the lens of Siyasah Dusturiyah (Islamic constitutional politics). The main issue addressed is the rising crime rate including motorcycle theft, gang violence, and street crimes that has caused public unrest. Employing a juridical-empirical approach with descriptive qualitative methods, data were gathered through observation, interviews, and documentation. The findings indicate that the Tasikmalaya Police have implemented both preventive (patrols, legal counseling, public education) and repressive (investigation and law enforcement) strategies. Community-based programs such as "Police, Friends of the People" and "Friday Dialogues" have also enhanced public-police cooperation. From a Siyasah Dusturiyah perspective, the police embody the role of muḥtasib, enforcers of amar ma’ruf nahi munkar, tasked with maintaining public welfare and order. Thus, police responsibility is both legally mandated and spiritually driven as a divine trust